Francisco Bilbao and the “danger” of fashion in South America - Goldwaser Yankelevich, Nathalie (Cuadernos de Historia, 2020)
In Latin America during the nineteenth century, the theme of fashion has been recurrent. Fashion understood as the introduction of novelty in the face of ancient customs. Based on the methodology proper to the “history of political concepts”, it is proposed to go through three texts, as a representative universe, in order to give an account of the original contributions of this Chilean author, Francisco Bilbao, has been one of the nineteenth-century thinkers who dedicated his life to problematizing the state of “independence” of nations in South America. His diagnosis implied demonstrating how the Catholic Church and the Hispanic cultural world generated the state of poverty, barbarism and abdication of thought. What are the therapeutics that he proposes to get out of this old and retarded culture? Bilbao proposes to introduce certain political fashions that, although they generate the “sensation of danger”, are the only ones that through education can modify the customs of a nation.